Improving the tensile ductility of metal matrix composites by laminated structure: A coupled X-ray tomography and digital image correlation study. (1st July 2017) - Fan, Guohua; Geng, Lin; Wu, Hao; Miao, Kesong; Cui, Xiping; Kang, Huijun; Wang, Tongmin; Xie, Honglan; Xiao, Tiqiao
Abstract: The microstructure design strategy of laminated structure was applied to improve the mechanical properties of metal matrix composites (MMCs). The laminated composites were prepared by hot pressing and rolling of alternately stacked Ti foils and SiCp /Al composite foils, and exhibited a superior strength-ductility synergy compared to SiCp /Al bulk MMCs. Coupling X-ray tomography and digital image correlation (DIC) revealed that the enhanced mechanical properties originated from the contribution of the interface on local stress/strain transfer behaviors, thus delaying the crack initiation and propagation within SiCp /Al layers. Graphical abstract: